Editorial: educational big data: extracting meaning from data for smart education - Chen, Nian-shing (2020)
Data are a valuable resource in education, with a panoply of applications across all educational levels, subjects and stakeholders. When data becomes overwhelming in terms of volume and complexity, innovative techniques are required to extract meaning and transform this data into valuable information. This special issue of the journal focuses on the value of Educational Big Data in the context of different education levels, from pre-school to higher education. The manuscripts included in this issue approach the potential of EBD for academic performance prediction, learning analytics implementation, and the identification and improvement of student behavioral patterns and performance. They are centred on students and emphasize the role that technology can play in improving their learning experience and performance.